2019
DOI: 10.4110/in.2019.19.e19
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric Nanoparticles Containing Both Antigen and Vitamin D3 Induce Antigen-Specific Immune Suppression

Abstract: The active form of vitamin D 3 , 1,25-dihydroxyvitamin D 3 (aVD 3 ), is known to exert beneficial effects in the treatment of autoimmune diseases because of its immunosuppressive effects. However, clinical application of aVD 3 remains limited because of the potential side effects, particularly hypercalcemia. Encapsulation of aVD 3 within biodegradable nanoparticles (NPs) would enhance the delivery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
(43 reference statements)
1
7
0
Order By: Relevance
“…Most importantly, VD3-raised DCs show tolerogenic stability in face of repeated rechallenge with pro-inflammatory stimuli, making VD3 a robust DC-tolerizing candidate in an already inflamed environment ( 163 ). In line with that, several recent studies in mice demonstrated that nanoparticles loaded with VD3 and OVA induced tolerogenic DCs with in vitro and in vivo suppressive capacity of OVA-specific T cells ( 164 , 165 ). Additionally, subcutaneous injection of VD3-loaded particles resulted in effective targeting of PD-L1 high draining lymph node DCs, resulting in amelioration of a RA disease model ( 165 ).…”
Section: Fostering Immune Tolerance With Dc-targeted Liposome Vaccinessupporting
confidence: 66%
“…Most importantly, VD3-raised DCs show tolerogenic stability in face of repeated rechallenge with pro-inflammatory stimuli, making VD3 a robust DC-tolerizing candidate in an already inflamed environment ( 163 ). In line with that, several recent studies in mice demonstrated that nanoparticles loaded with VD3 and OVA induced tolerogenic DCs with in vitro and in vivo suppressive capacity of OVA-specific T cells ( 164 , 165 ). Additionally, subcutaneous injection of VD3-loaded particles resulted in effective targeting of PD-L1 high draining lymph node DCs, resulting in amelioration of a RA disease model ( 165 ).…”
Section: Fostering Immune Tolerance With Dc-targeted Liposome Vaccinessupporting
confidence: 66%
“…Cellular targets for immune suppression include APCs 261 , autoreactive T cells and B cells 262 , and regulatory T cells and B cells 263 , 264 . Antigen-specific immunotherapy aims to reprogramme or reduce reactive cells or impart them with tolerance to certain antigens 260 .…”
Section: Nps In Precision Medicinementioning
confidence: 99%
“…NPs that deliver IL-2 and TGFβ can expand the number of regulatory T cells in vivo, suppressing the symptoms of lupus 263 . The active form of vitamin D 3 has immunosuppressive effects because it modulates dendritic cell function 261 . Active vitamin D 3 can cause hypercalcaemia when administered systemically, so NP delivery is a promising alternate strategy.…”
Section: Nps In Precision Medicinementioning
confidence: 99%
“…In previous reports, to improve the antigen-specific immune tolerance, autoantigen-encapsulated/conjugated nano/microparticles were additionally loaded with various immunosuppressive molecules including aryl hydrocarbon receptor 13 , 51 , 52 , anti - inflammatory cytokines 53 55 , immunosuppressive ligands and gene 56 58 , autoantigen - loaded MHC 56 , or immunosuppressive small molecules such as rapamycin 15 , 16 and vitamin D3 59 . These agents direct DCs and T cells in various immunological pathways to establish immune tolerance 60 .…”
Section: Discussionmentioning
confidence: 99%